2006
DOI: 10.1177/1077558706290941
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Efficiency of Home-Based Nursing Health Promotion for Older People: A Review of the Literature

Abstract: Sammendrag:Despite the large potential role that community nurses have in providing individualized health promotion to older people, there is a lack of consensus in the literature regarding this role's effectiveness and efficiency. This article presents a literature review and synthesis of 12 randomized controlled trials selected from 344 published studies on preventive home visitation programs for older people. The findings suggest that a diversity of home visiting interventions carried out by nurses can favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
139
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 61 publications
(284 reference statements)
3
139
1
4
Order By: Relevance
“…Because of the inconsistent results more research is needed to understand if, and under what circumstances, case management can be effective (Latour et al, 2007;Lupari et al, 2011;Oeseburg et al, 2009;Onder et al, 2007). Reasons for the inconclusive results could be the lack of an established definition and content of the concept of case management and that the interventions are rarely described in detail, making it difficult to compare different case management interventions (Markle-Reid et al, 2006;van Haastregt et al, 2000). Another source of differences in outcomes may be due to differences in samples and settings (Hallberg & Kristensson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the inconsistent results more research is needed to understand if, and under what circumstances, case management can be effective (Latour et al, 2007;Lupari et al, 2011;Oeseburg et al, 2009;Onder et al, 2007). Reasons for the inconclusive results could be the lack of an established definition and content of the concept of case management and that the interventions are rarely described in detail, making it difficult to compare different case management interventions (Markle-Reid et al, 2006;van Haastregt et al, 2000). Another source of differences in outcomes may be due to differences in samples and settings (Hallberg & Kristensson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several of the included components have been postulated in reviews as promising components of interventions to prevent functional decline in communitydwelling older people (Daniels et al 2010;Markle-Reid et al 2006). The [G]OLD-protocol applies a stepwise approach.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, 10 systematic reviews of the clinical effectiveness of home-or community-based programmes have been published. [6][7][8][9][10][11][12][13][14][15] However, these reviews have reported inconsistent and conflicting results. Subgroup analyses of the largest published meta-analysis suggested that effective homevisiting programmes include multidimensional assessment and numerous follow-up visits and were targeted at individuals who were at lower risk of death.…”
mentioning
confidence: 99%